Effect of altitudinal variation on the soil characteristics in sal (Shorea robusta gaertn.) forests of eastern Nepal - Bhattarai, Krishna Prasad; Mandal, Tej Narayan (Our Nature, 2017)
Physico-chemical properties of forest soil depends on a variety of natural factors, the most important are variation in altitude, vegetation cover and microbial activities. The present study was conducted to understand the effect of variation in altitude in the soil characteristics in Tarai Sal forest (TSF) and Hill Sal forest (HSF), of eastern Nepal. Soil samples were collected from thirty plots randomly in each forest from 0- 15cm and 15-30cm depths in May 2012. Both forests had sandy loam type of soil texture. However, the percentage composition of soil particles varies within the forest sites. Soil moisture was higher in TSF. It was maximum in the rainy season in both forests. Water holding capacity was slightly higher in TSF. Bulk density was higher in TSF and it increased with soil depth in both forests. The pH value was slightly higher in HSF than TSF however, the value increased in lower soil depth in both forest stands. In the upper soil layer (0-15cm) soil organic carbon (SOC) was higher in HSF (2.09%) than TSF (1.6%). Similarly, total nitrogen (TN) was also higher in HSF (0.173%) than in TSF (0.129%) while total phosphorus (TP) was more or less same in both forest stands. The potassium (K) a soil extractable nutrient also showed higher value in HSF (312.13 µg g-1) than TSF (238.47 µg g-1). The values of SOC, TN, TP and K decreased in lower depth (15-30cm) in both forest stands. In conclusion, variation in altitude causes difference in the microclimatic condition which resulted into the alternation in soil characteristics. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.